Nanocellulose based titanium dioxide nanocomposites for the wastewater treatment of textile industry - Khan, Shahid Ali; Rafiq, Muhammad Tariq; Feng, Ying; Ali, Hayssam M.; Alsakkaf, Waleed A. A.; Shah, Farzana Altaf; Ali, Attarad; Ahmed, Temoor; Aziz, Rukhsanda (Frontiers in Environmental Science, 2025)
Nanocellulose based titanium dioxide nanocomposite (NC/TiO2) with enhanced adsorption and photocatalytic properties is a favorable material for treating wastewater of textile industry. The NCTiO2 nanocomposite was fabricated by a two-step hydrothermal process and characterized through X-ray diffraction (XRD), Fourier-transform infrared-spectroscopy (FT-IR), Field emission scanning electron microscopy (FE-SEM), and Ultraviolet-visible absorption spectroscopy (UV-Vis Absorption Spectroscopy) techniques. The maximum percentage removal efficiencies under optimum experimental conditions for total dissolved solids total salts, turbidity, chemical oxygen demand (COD), and color in textile industry A and textile industry B were observed to be 49.16% and 65.05%, 74.98% and 80.64%, 97.48% and 100%, 87.18% and 92.03%, and 75.58% and 93.86%, respectively. The maximum photocatalytic degradation efficiencies for the removal of turbidity, COD and color in textile industry A and textile industry B were observed to be 96.21% and 99.66%, 85.82% and 87.43%, and 76.60% and 95.82%, respectively. Due to low initial concentration values of treatment parameters, the adsorption and photocatalytic removal efficiencies of textile industry B were higher as compared to textile industry A. The current study suggests that NC/TiO2 has the potential to be used as a highly efficient adsorbent and photocatalyst for removing pollutants from wastewater.